Classification of diabetic foot disease using the WIfI system and related factors: a study at Cho Ray hospital - Huynh, Le Thai Bao; Nguyen, Hai Thuy; Tran, Huu Dang (Tạp chí Y Dược Huế, 2026)
Background: To describe the characteristics of Wound, Ischemia, and foot Infection (WIfI) classification in diabetic patients with foot complications. To analyze risk factors associated with WIfI clinical stages in this population. Materials and Methods: A cross-sectional descriptive study was conducted on 207 diabetic patients with foot disease at Cho Ray Hospital from April 2023 to April 2024. Results: According to the WIfI classification, the distribution of limb amputation risk across clinical stages was 6.8% for Stage 1 (very low risk), 10.1% for Stage 2 (low risk), 19.8% for Stage 3 (moderate risk), and 63.3% for Stage 4 (high risk). Factors significantly associated with WIfI clinical stages included clinical parameters such as infection (p < 0.001), tissue loss (p < 0.001), loss of protective sensation (LOPS) assessed by monofilament (p < 0.01), tuning fork (p < 0.05), and the Ipswich Touch Test (p < 0.05). Laboratory and hemodynamic indicators included HbA1C (p < 0.05), Toe-Brachial Index (TBI) (p < 0.05), and Toe Pressure (TP) (p < 0.001). The regression model was defined by the equation: Amputation Risk = 0.830 + 0.065HbA1c - 1.048ABI + 0.862*TBI. Conclusions: The WIfI classification system should be implemented for the assessment of diabetic foot disease in Vietnam, with particular clinical attention to TP and Ankle-Brachial Index (ABI) values.